Transparency and Performance of Central Banks ASEAN countries - Nurida Fitriani; Dita Dismalasari Dewi (Jurnal Ilmiah Raflesia Akuntansi, 2026)
This paper delves into the increasingly prominent role of central bank transparency in modern monetary policy. It analyzes both theoretical and practical aspects of transparency, examining various methods employed by central banks and assessing the empirical evidence surrounding their effectiveness. The research adopts a structured approach, reviewing theoretical literature on the impact of transparency on both the consequences and performance of monetary policy. It proposes a novel distinction between uncertainty and incentive effects of transparency, providing valuable insights into its nuanced nature. Empirically, the paper utilizes panel data regression with fixed effects to construct a comprehensive index of central bank transparency encompassing political, economic, procedural, policy, and operational aspects. This index is then applied to ten major central banks in ASEAN countries, revealing a diverse landscape of transparency levels and dynamics through detailed analysis of actual information disclosure practices. The key finding suggests a nexus between transparency on inflation, GDP and Interest rate demonstrating that greater openness translates to enhanced effectiveness. Additionally, identifies the Bank of Thailand as the most transparent central bank within the studied group, followed by the Philippines, Indonesia, Singapore, and Malaysia. Laos and Cambodia, conversely, emerge as the least transparent.